International investment agreements : flexibility for development (UN New YorkUS, 2000)
Examines ways in which international investment agreements (IIAs) can provide for flexibility with a view towards promoting development, while encouraging FDI and providing stability and predicatability investment relations. Discusses briefly the meaning and purpose of flexibility in the interest of development in the context of IIAs. Looks at how existing IIAs have provided for flexibility from four main angles: the objectives of an agreement, its overall structure and modes of participation, its substantive provisions and its application.
Keywords: INVESTMENT